2016
DOI: 10.4062/biomolther.2016.006
|View full text |Cite
|
Sign up to set email alerts
|

Procaine Attenuates Pain Behaviors of Neuropathic Pain Model Rats Possibly via Inhibiting JAK2/STAT3

Abstract: Neuropathic pain (NPP) is the main culprit among chronic pains affecting the normal life of patients. Procaine is a frequently-used local anesthesia with multiple efficacies in various diseases. However, its role in modulating NPP has not been reported yet. This study aims at uncovering the role of procaine in NPP. Rats were pretreated with procaine by intrathecal injection. Then NPP rat model was induced by sciatic nerve chronic compression injury (CCI) and behavior tests were performed to analyze the pain be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…The activated signaling pathway is accompanied by increased sensitivity to thermal and cold stimulations, indicating the aggravated pain behavior. These results support the fact that this cue is associated with neuropathic pain regulation (Li, Yan, Yu, & Duan, ). Therefore, the decreased content of IL‐6 by using MSCs could abate in turn the protein expressions of its downstream molecule p ‐JAK2 and consequently p ‐STAT3 (Al‐Massri et al, ).…”
Section: Mscs Therapy In Cipn and Peripheral Neuropathysupporting
confidence: 85%
“…The activated signaling pathway is accompanied by increased sensitivity to thermal and cold stimulations, indicating the aggravated pain behavior. These results support the fact that this cue is associated with neuropathic pain regulation (Li, Yan, Yu, & Duan, ). Therefore, the decreased content of IL‐6 by using MSCs could abate in turn the protein expressions of its downstream molecule p ‐JAK2 and consequently p ‐STAT3 (Al‐Massri et al, ).…”
Section: Mscs Therapy In Cipn and Peripheral Neuropathysupporting
confidence: 85%
“…JAK2/STAT3 signal transduction is involved in the activation of glial cells and formation of neuropathic pain [ 13 ]. In the CCI model, the presence of neuropathic pain was accompanied by the high expression of JAK2 and STAT3, and the inhibition of the expression of these factors could significantly relieve pain [ 14 ]. Ion channel dysfunction is central to the pathogenesis of painful DNP.…”
Section: Discussionmentioning
confidence: 99%
“…WP1066, as a STAT3 inhibitor can serve as a novel therapeutic agent in bCCI neuropathic pain rats (Xue et al, ). Down‐regulation of miR‐218 can relieve neuropathic pain by inhibiting STAT3 signaling activation in microglial cells (Li et al, ; Li & Zhao, ). In our study, we found that STAT3 was a target of miR‐544 and STAT3 over‐expression can lead to neuropathic pain development.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that microRNA‐93 is able to relieve neuropathic pain via inhibiting STAT3 (Yan et al, ). Procaine can suppress neuropathic pain in model rats through targeting JAK2/STAT3 (Li, Yan, Yu, & Duan, ).…”
Section: Introductionmentioning
confidence: 99%